Navigating racism: A scoping review of barriers in the experiences of Black Health Professions students - Monica L. Miles; Terrell R. Morton; Philip Pettis; Ramar Henderson; Carl A. Frizell; Vanessa S. Bester; Aisha K. O’Mally; Logan Trevino-Fica (Discover Education)
Abstract This manuscript examines the racism experienced by Black students in health professions through a scoping review of 33 articles. The analysis reveals significant gaps in the literature across multiple dimensions of racism, including interpersonal, community, institutional and systemic levels. Interpersonal racism, identified in 30% of the studies, demonstrates how discriminatory interactions negatively affect students' academic performance and overall well-being. Community racism, addressed in 24% of the studies, highlights the role of community norms in fostering exclusion and stereotype threat. Institutional racism was minimally addressed, appearing in only 3% of the studies, and focusing primarily on barriers posed by standardized testing. Systemic racism and historical factors received limited attention, with 52% of the studies failing to adequately connect these broader forces to the racialized experiences of Black students. Addressing these gaps is essential for shaping policies that dismantle structural barriers, promote equitable admissions, and expand funding for initiatives that support Black students pursuing health professions. Prioritizing these efforts is critical to creating a more inclusive educational environment, improving student outcomes, and reducing health disparities.